FUN OUTBOUND AS A HOLISTIC LEARNING STRATEGY TO SUPPORT GROSS MOTOR DEVELOPMENT IN EARLY CHILDHOOD: A NARRATIVE STUDY IN TK ABA BAYEN: Outbond, Motoric Skills, Early Chillhood - Pashela, Perdana; Zarkasih, Khamim; Suharti (PG PAUD Universitas Negeri Surabaya, 2025)
Outbound activities offer an experiential and play-based approach to physical learning that supports the development of gross motor skills in early childhood. This study aims to explore how outbound activities contribute to the physical, social, and emotional growth of children aged 5–6 years at TK ABA Bayen. Using a narrative inquiry approach, the research captures the lived experiences of children, teachers, and parents during the outbound program involving activities such as rope bridge walking, throwing the glass, fits hands and feet, relaying water and crossing suspension bridge. Data were collected through observations, reflective journals, and interviews, and analyzed thematically to reveal patterns of growth and meaning-making. The findings indicate that outbound activities foster noticeable improvements in children’s balance, strength, coordination, and overall confidence in movement. Beyond physical gains, the narratives also highlight enhancements in self-confidence, social-emotional and social interaction. The study concludes that outbound activities, when intentionally designed and facilitated, serve as a powerful medium for holistic development in early childhood. It is recommended that early childhood education institutions integrate outbound activities into the learning environment to support children's physical and psychosocial growth through embodied, meaningful experiences.